Entrepreneurs of color in Wisconsin: Bridging the gap in resources to mobilize potential. Issue 2 (15th March 2021) - Hammer, Diana; Malual, Joseph
ABSTRACT: Despite their substantial contribution to economies, little is known about how entrepreneurs of color in rural areas leverage resources to start ventures. This study examined the experiences of these entrepreneurs in securing information and financial capital at startup. Using the Community Capital Framework as an analytical tool, we take a systems approach to highlight the influence of contextual factors impacting the entrepreneurs and their contributions to the economy. We conducted interviews with 35 entrepreneurs to explore their experiences of operating businesses in Wisconsin. Results indicate entrepreneurs face barriers to accessing financing, information, and facilitating business networks. While they reported positive views of the community, they are mostly excluded from business organizations and heavily rely on bonding social capital involving kinship and friends and human capital for leveraging information and financial capital. This research provides important insights for policymakers and practitioners in rural areas hoping to develop vibrant inclusive economies.